Revealing the unspoken battle: limited awareness of PMDD and Its invisible consequences on women’s well-being in Pakistan - Shahzad, Muhammad; Saeed, Mahnoor; Shahzad, Farah; Rabia; Hassan, Ali (Journal of the Pakistan Medical Association, 2025)
Premenstrual Dysphoric Disorder (PMDD) is a reproductive endocrine-related mood disorder that arises in the late luteal phase and diminishes with menses. It involves significant emotional and physical symptoms occurring weeks before menstruation, severely impacting daily life and well-being, representing an intensified form of PMS. PMDD varies between 1.2% to 5% among women in their reproductive years [1]. The symptoms significantly affect women’s capacity to participate in school, partake in regular social activities, and maintain productivity in the workplace [2]. On a global scale, women are twice as prone to experiencing depression in comparison to men. Compared to the general population, females diagnosed with PMDD exhibit a significantly elevated risk of bipolar disorder (BD). Factors such as age, level of education, economic circumstances, and exposure to verbal or physical violence can exacerbate depressive symptoms in women [3]. New findings indicate that PMDD raises the likelihood of experiencing perinatal depression [1]. There is also a connection between PMDD and suicidal thoughts, intentions, and suicide attempts. As per a recent study, around 40% of women diagnosed with PMDD reported instances of suicidal thoughts [4]. PMDD frequently goes undetected by healthcare professionals, can pose challenges in terms of diagnosis, and falls within the overlap of gynaecology and psychiatry which also often impose challenges in its diagnosis and treatment. According to the Pakistan Bureau of Statistics (PBS), females constitute 49% of the total population, with 22.33% falling within the 15-45 age range, corresponding to the reproductive age (Pakistan Bureau of Statistics 2012-2013) [5] Although research in Pakistan has delved into how PMS affects the quality of life, there’s a shortage of data on PMDD’s influence due to societal taboos surrounding discussions about women’s menstrual health in the conservative society. A recent investigation involving female medical students at Fatima Jinnah Medical University unveiled a notably high occurrence of PMDD among them, specifically at a rate of 12.1%. PMDD has had detrimental effects on both the physical well-being and work productivity of these students, concurrently leading to a significant decline in their psychological health [2]. Addressing PMDD in Pakistan requires urgent diagnosis, awareness campaigns, and education on its impact on women’s health and daily life. Media efforts should tackle taboos, especially among men, while targeted initiatives in rural areas improve access to care. Medical professionals must be trained to treat PMDD and recognize suicidal tendencies. Further research is essential to understand its scope.